2016
DOI: 10.1038/jid.2015.409
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs in Psoriasis

Abstract: Psoriasis is a chronic inflammatory skin condition resulting from a complex interplay among the immune system, keratinocytes, susceptibility genes, and environmental factors. However, the pathogenesis of psoriasis is not completely elucidated. microRNAs represent a promising class of small, noncoding RNA molecules that function to regulate gene expression. Although microRNA research in psoriasis and dermatology is still relatively new, evidence is rapidly accumulating for the role of microRNAs in the pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
109
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 85 publications
1
109
0
1
Order By: Relevance
“…Numerous studies have focused on the assessment of miRNA expression and have shown considerable changes in their expression profiles in various diseases (17)(18)(19)(20), although the most remarkable changes have been observed in cancer (21)(22)(23)(24). The results of these studies point to the profiling of miRNA expression as an important tool for the prognosis, diagnosis and treatment of diseases (18,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on the assessment of miRNA expression and have shown considerable changes in their expression profiles in various diseases (17)(18)(19)(20), although the most remarkable changes have been observed in cancer (21)(22)(23)(24). The results of these studies point to the profiling of miRNA expression as an important tool for the prognosis, diagnosis and treatment of diseases (18,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…In psoriasis, miRNA expression disorders have been reported [31, 32]. To date, more than 250 miRNAs have been reported as aberrantly expressed in psoriasis tissue, the majority of which are found in peripheral blood or involved psoriatic skin, but only small subsets of these dysregulated miRNAs in psoriasis have confirmed mRNA targets with established biological functions in the skin [19]. In the present study, we determined the expression level and detailed function of miR-150, which was reported to be down-regulated in psoriasis tissues [20].…”
Section: Discussionmentioning
confidence: 99%
“…Basically, miRNAs exert their functions through binding to the 3’UTR of target mRNA genes and subsequently disrupts translation or triggers mRNA degradation [19]. Excessive proliferation of keratinocytes in psoriasis causes local environmental hypoxia, leading to increased expression of HIF-1α [12]; microenvironment hypoxia accelerates vascular growth to supply the oxygen required for cell growth, along with the elevated expression of VEGFA during this process [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Interestingly, aberrantly expressed miRNA are disclosed to be involved in regulation of hyperproliferation, abnormal differentiation of keratinocytes and disordered activation of immunity. 5,6 Interestingly, aberrantly expressed miRNA are disclosed to be involved in regulation of hyperproliferation, abnormal differentiation of keratinocytes and disordered activation of immunity.…”
Section: Introductionmentioning
confidence: 99%